Flocculation, cell surface hydrophobicity and 3‐OH oxylipins in the SMA strain of Saccharomyces pastorianus. Issue 1 (9th January 2015) - Potter, Greg; Budge, Suzanne M.; Speers, R. Alex
<x xml:space="preserve">Abstract</x> Three‐hydroxy‐oxylipins (3‐OH oxylipins) have been previously detected in brewing yeast production strains at flocculation onset. In this work, the SMA strain of Saccharomyces pastorianus was characterized during growth in a miniature fermentation assay by measuring flocculation and cell surface hydrophobicity (CSH). Proportions of 3‐OH oxylipin were also measured concurrently during growth in the miniature fermentation assay and a defined 3‐OH oxylipin extraction protocol using ethyl acetate is presented along with a novel derivatization and gas chromatography–mass spectrometry (GC‐MS) detection approach. When the SMA strain was grown in the assay, near maximal CSH and flocculation levels were achieved by a 36 h fermentation time. Under the same culture conditions, the oxylipin 3‐OH decanoic acid (3‐OH 10:0) was identified. This oxylipin could not be detected early in the fermentation, but elevated relative levels of 3‐OH 10:0 were reached by 36 h, coinciding with increased CSH levels. It was previously presumed that the formation of 3‐OH oxylipins at flocculation onset might increase the CSH. However, results from this study suggest that 3‐OH 10:0 may not contribute to cell wall hydrophobicity. The flocculation behaviour of the SMA strain was also monitored in the presence of 3‐OH 10:0, but exposure to this oxylipin did not impact the sedimentation of this yeast, suggesting that 3‐OH oxylipins may not act as mediators of quorum sensing in this strain. Copyright © 2015 The Institute of Brewing & Distilling